2022
DOI: 10.3389/fonc.2022.975981
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils: Musketeers against immunotherapy

Abstract: Neutrophils, the most copious leukocytes in human blood, play a critical role in tumorigenesis, cancer progression, and immune suppression. Recently, neutrophils have attracted the attention of researchers, immunologists, and oncologists because of their potential role in orchestrating immune evasion in human diseases including cancer, which has led to a hot debate redefining the contribution of neutrophils in tumor progression and immunity. To make this debate fruitful, this review seeks to provide a recent u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 346 publications
0
13
0
Order By: Relevance
“…Thus, beside their role as unspecific biomarkers of an inflammatory profile, neutrophils deserve investigation to unravel the specific mechanisms driving their prognostic and predictive roles, to control them in a therapeutic perspective. Indeed, several approaches for neutrophil antagonism are under investigation to potentiate immune checkpoint blockade [ 31 ]. In human studies, neutrophils are identified as CD66b+, CD15+ CD14−, and CD33+ white blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, beside their role as unspecific biomarkers of an inflammatory profile, neutrophils deserve investigation to unravel the specific mechanisms driving their prognostic and predictive roles, to control them in a therapeutic perspective. Indeed, several approaches for neutrophil antagonism are under investigation to potentiate immune checkpoint blockade [ 31 ]. In human studies, neutrophils are identified as CD66b+, CD15+ CD14−, and CD33+ white blood cells.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Much attention has been paid to the role of neutrophils in tumor immunity. 11 , 33 Some studies showing that neutrophils and granulocyte colony-stimulating factor promote tumor development 34 , 35 and others pointing out that the effector function of neutrophils is related to antitumor immune suppression. 11 , 36 Recent studies have found that the neutrophil precursors PMN-MDSCs are vulnerable to ferroptosis which promotes the suppression of tumor immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no evidence linking IGFBP1 with ferroptosis in lung cancer cells, but early studies have shown that IGFBP1 protein can be efficiently cleaved by enzymes secreted by immune cells, such as central granulocyte-derived proteases cathepsin G and elastase, in vitro and in vivo. 34 Tumor hypoxia and inflammatory infiltration provide strong support for the aggregation and activation of central granulocytes. 38 Our preliminary study also showed that LUAD is associated with the infiltration of PMN-MDSCs with ferroptosis fragility.…”
Section: Discussionmentioning
confidence: 99%
“…The mature neutrophil population MMP9, expressing immunosuppressive markers showed higher frequency in the control group and therapeutic vaccine alone group compared to the mice that received the sequential treatment. These neutrophils have been stated to have potent immunosuppressive capabilities in oncology (37). The same might be true in the context of chronic infection, where it has been described that HBV may reduce neutrophil responses (38).…”
Section: Discussionmentioning
confidence: 99%